INNOVATION AND CHALLENGES IN HIGHER EDUCATION: PURSUING EXCELLENCE AND RELEVANCE IN THE GLOBAL ERA - Kardi Kardi; Hemi Pamuraharjo, Nawang Kalbuana (International Journal of Teaching and Learning, 2024)
This research was conducted through the literature review method, by finding references in accordance with the research context. The purpose of this research is to summarize the current findings and provide an overview of how higher education institutions pursue academic excellence and industry relevance amid global challenges. The results revealed that higher education institutions are implementing innovations such as multidisciplinary curricula, expanded use of online learning, and university-industry collaboration initiatives to promote research and development. The research found that success in supporting excellence and relevance depends on institutions' ability to strategically adapt to external changes and utilize technological advances for innovative and responsive educational development. The implications include the need for dynamic policies and resource utilization to support an academic environment that encourages students' intellectual growth and professional competence.